Inconsistent Effects of Iron-Folic Acid and/or Zinc Supplementation on the Cognitive Development of Infants - Siegel, Emily H; Kordas, Katarzyna; Stoltzfus, Rebecca J; Katz, Joanne; Khatry, Subarna K; LeClerq, Steven C; Tielsch, James M (Journal of Health, Population and Nutrition, 2012)
Despite concerns over the neurocognitive effects of micronutrient deficiencies in infancy, few studies have examined the effects of micronutrient supplementation on specific cognitive indicators. This study investigated, in 2002, the effects of iron-folic acid and/or zinc supplementation on the results of Fagan Test of Infant Intelligence (FTII) and the A-not-B Task of executive functioning among 367 Nepali infants living in Sarlahi district. Infants were enrolled in a cluster-randomized, placebo-controlled clinical trial of daily supplementation with 5 mg of zinc, 6.25 mg of iron with 25 μg of folic acid, or zinc-iron-folic acid, or placebo. These were tested on both the tasks using five indicators of information processing: preference for novelty (FTII), fixation duration (FTII), accelerated performance (≥85% correct; A-not-B), deteriorated performance (<75% correct and >1 error on repeat-following-correct trails; A-not-B), and the A-not-B error (A-not-B). At 39 and 52 weeks, 247 and 333 infants respectively attempted the cognitive tests; 213 made an attempt to solve both the tests. The likelihood of females completing the A-not-B Task was lower compared to males when cluster randomization was controlled [odds ratio=0.67; 95% confidence interval 0.46-0.97; p<0.05]. All of the five cognitive outcomes were modelled in linear and logistic regression. The results were not consistent across either the testing sessions or the information-processing indicators. Neither the combined nor the individual micronutrient supplements improved the performance on the FTII or the A-not-B Task (p>0.05). These findings suggest that broader interventions (both in terms of scope and duration) are needed for infants who face many biological and social stressors. DOI: http://dx.doi.org/10.3329/jhpn.v29i6.9896 JHPN 2011; 29(6): 593-604